Inventory of Local Food Plants in Banceuy Traditional Village, Subang Regency, West Java, Indonesia - Raihandhany, Reza; Purnomo, Purnomo (-, 2025)
Plants are one of the most important food resources for human civilization. The Sundanese people of West Java, Indonesia are well known for consuming raw plants as part of their food culture called lalapan. West Java consists of several traditional villages, one of them is Banceuy Traditional Village which is located in Subang Regency. No prior ethnobotanical study of local food plants in Banceuy Traditional Village has been recorded. Therefore, this study aims to document the diversity of local food plants in Banceuy Traditional Village and the indigenous people’s knowledge in local food plant utilization. This study used semi-structured interviews with 32 informants that consisted of 2 key informants and field-guided observation which was accompanied by one of the key informants around the village to identify and collect the food plant specimens. Banceuy indigenous people utilized 160 local food plant species belonging to 55 families. Fabaceae, Cucurbitaceae, Solanaceae, and Zingiberaceae were the dominant food plant families. Herbs and tree respectively were the dominant food plant habits. These plant species were utilized as sources of carbohydrates, fruits, vegetables, spices, seeds, and beverages. Fruits were the most utilized plant parts while vegetables were the most food plant categories, because some of the fruits were consumed directly as lalapan or processed through sauté cooking as vegetables. Banceuy indigenous people have a close relationship with plants as they utilize those plant species for daily food consumption.